PERIODE KRITIS TANAMAN KEDELAI TERHADAP PERSAINGAN GULMA - Hendrival Hendrival; Zurrahmi Wirda; Abdul Azis (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2014)
The research was aimed at determining a critical period of soybean in competition with weeds. The experiment was conducted in Seunebok Baro Village, Sub-District Cot Girek, District Aceh Utara, from January to May 2013. The experiment was arranged in a randomized complete block design. Factor evaluated was a period weed competition with 14 levels and three replications. Variables observed were growth plant component, yield component, and weed compositions. The results showed that period weed competition affected growth plant component and yield component. Critical period of soybean variety Kipas Merah in competition with weeds occurred at 2 - 6 weeks after planting. Dominant weed species were Dichrocephala integrifolia, Mimosa pudica, Ipomoea triloba, Ageratum conyzoides, Cleome rutidosperma, and Axsonopus compressus. Minimum scale of weed control for soybean variety Kipas Merah can be carried out from 2 until 6 weeks after planting for preventing yield loss.